The Economics of Federal Credit Programs - Bosworth, Barry P.; Carron, Andrew S.; Rhyne, Elisabeth H. (Rowman & Littlefield Publishers, 2010)
The Economics of Federal Credit Programs discusses government lending, government guaranty of loans, and credit control in the United States.